Quandoque bonus dormitat Homerus: theology and education in Plato’s Republic and the Oratio ad adolescentes of Saint Basil - Casallas-Villate, Andrés (Byzantion Nea Hellás, 2024)
The link between Platonism and early Cristian thought has been noted amply in so far the influence the former has had on the latter. This tremendous influence is evident in the philosophical platonic vocabulary that the Cristian thinkers will use. It has also been established an almost perfect analogy between some constructions of the platonic “philosophic system” and the speculative theological edifice that began to be developed after God’s death in the Cross. However, the analogy is not perfect and not all of Plato’s philosophical elements are compatible with the doctrine of Jesus Christ. This article discusses some points in common and some differences that seem to be present between platonic metaphysics, theology and politics in The Republic (books II and III) and the sketch of Christian theology in Basil’s Oratio ad adolescentes. Especially, those with respect to Homer’s role as an educator and the moral and political results of the mythological works of the Greek poets. Thus, the necessity for the polis, in the case of Plato, of stories that reflect true theological principles and the convenience of stories that encourage Christian youth to practice virtue, in the case of Basil.